Zakat dan Pajak sebagai Lembaga Keuangan Publik - Rini Rizkiyana Ulfa; Yudi Dwi Ariyanto (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Zakat plays an important role in public finance. The “public” concept of zakat makes it a special institution. Zakat is imposed on the Muslim public and is channeled back only to the Muslim public. Zakat also has a political and ritual character. Especially related to property that can be easily hidden. This also explains why Abu Bakr did not fight those who avoided zakat on money. He did not want to enter an area that was not his territory. In terms of hidden wealth, the people are free to carry out this obligation or not. In other words, this is their business with Allah. The concept of real and hidden wealth determines the political and ritual character of zakat and also determines the changing role of the government in using its political power. These are some important points that are discussed in the book al-Amwal by Abu Ubaid.